The role of independent curriculum policy in improving character education in the 4.0 era in Indonesia - Alika Rema putri; Yupita Dwi Saputri; Denny Prayuda; Hansein Arif Wijaya (Edumaspul: Jurnal Pendidikan, 2024)
This article aims to see how the 4.0 era or the industrial era and also this technology affects the character of students in Indonesia as well as the role of independent curriculum policies in addressing student character education and still being able to master technology which is a global need. This research uses a process similar to a review literature or studies. Collecting references from many previous studies and combining them to produce findings is one method of conducting literature studies (Mardalis, 1999). There are various strategies that can be used to carry out the process of changing student characteristics through digital learning to develop their reading comprehension skills through the use of comprehension software. reading.In the context of the era of globalization and technological progress, education has a vital role in shaping the character of students who are strong and ethical. Challenges do not only come from the pandemic, but also from the industrial revolution and technological developments in the digital era, which affect the way we learn and interact . The independent learning policy - independent campus is an effort to enable the development of creativity and skills that are relevant to the demands of the ever-changing world of work. Through this approach, we can strengthen character values ​​such as nationalism, religiosity, independence, integrity and mutual cooperation, thereby helping students to face the era of disruption better.